On the Problem of the Origin of the Armenian Dialectal Sound Sequence ուվա - AVETYAN, SARGIS (Bulletin of Yerevan University B: Philology, 2021)
The present article deals with the origin of the vowel ու in dialectal forms like չուվան, տուվալ. It is usually assumed that the vowel ու goes back to the vowel ը (e.g. չուվան ուվ (that is, the assimilative change ը >ու, caused by labiodental վ ) in dialects. The above mentioned traditional view is challenged by some researchers on the basis of certain dialectal forms which have not undergonethe change ըվ >ուվ (e.g. հավ - հըվէ՛րան, սէվ - սըվ/ւըցնի՛լ), and it is believed that the sound sequence ուվ is not anything else but reflection of the corresponding glide of earlier diphthongs. However, the latter assumption is not borne out by dialectalevidence, whereas a number of indisputable facts are in favour of the phonetic development ըվ >ուվ. A special note should be taken of the restricted and irregular nature of the change ըվ >ուվ, which accounts for also the unchanged forms հավ - հըվէ՛րան, սէվ - սըվ/ւըցնի՛լ and the like.
Keywords: dialectal sound sequence, dialectal forms, assimilative change, glide of earlier diphthongs, monophonemic diphthong, biphonemic diphthong